Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 3; b = -2; c = -1


= 3. - 1 = - 3


And either of their sum or difference = b


= - 2


Thus the two terms are - 3 and 1


Difference = - 3 + 1 = - 2


Product = - 3.1 = - 3




3x(x-1) + 1(x-1) = 0


(x-1)(3x + 1) = 0


(x-1) = 0 or (3x + 1) = 0


x = 1 or x = (-1)/3


Roots of equation are 1, (-1)/3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics